When it's neighbor's fault, a complicated ascending aortic aneurysm mimicking pulmonary embolism: A case report. Issue 1 (July 2022) - Bruno, Elvira; Caramia, Remo; Mangini, Francesco; Giaccari, Rinaldo; Santoro, Silvia; Galiano, Ludovico; Villano, Roberto Del; Muscogiuri, Eluisa; Amorese, Lillà; Zaccaria, Salvatore; Biederman, Robert W.W.
Abstract: Thoracic aortic aneurysms represent a potentially life-threatening disease with increasing prevalence, probably related to the increasing mean age of the global population; the complications of thoracic aortic aneurysms can show multiple modes of presentation in the acute phase based on various factors, including the involvement of the structures with which the aneurysm is in close anatomical relationship. With this case report we want to show how it is possible that a complicated ascending aortic aneurysm can mimic an acute pulmonary embolism/acute cor pulmonale in the acute phase; the earliest possible differential diagnosis between pulmonary embolism and acute aortic disease is of crucial importance due to the opposite implications that the treatment of these two diseases have. <Learning objective: Aortic acute syndromes may mimic acute cor pulmonale; the principal aim is to raise the readers' awareness of this aspect as the earliest possible differential diagnosis between pulmonary embolism and acute aortic disease is of crucial importance due to the opposite implications that the treatment of these two diseases has.>